AN ANALYSIS OF FLOUTING MAXIM IN EFL CLASSROOM INTERACTION - Asri Dwi E.S. (Vision: Journal for Language and Foreign Language Learning, 2015)
The present study concerns with the fl outing maxim occurredin EFL classroom interaction. It was aimed at investigating howthe conversational implicatures especially fl outing maxim are be-ing formed in teacher and students dialog during EFL teaching andlearning process. The present study used qualitative approach. Thedata taken from teacher and students interaction in EFL classroomare being transcribed and analyzed by categorizing utterances basedon the fl outing of maxim theory proposed by H.P. Grice. Based onthe data analysis, it has been discovered that during the conversa-tion, all speakers happen to be successful in observing maxims. Theproportion of non-observance maxim is only 2%. Sorts of maximthat is fl outed by speaker are maxim of quantity, quality and man-ner. The fl out of maxim is done by students because of their lackof linguistic and actional competence.